LITERASI MAHASISWA TERHADAP KONSEP GREEN ACCOUNTING DAN DAMPAKNYA PADA KUALITAS LULUSAN MAHASISWA AKUNTANSI DI UNIVERSITAS BUANA PERJUANGAN KARAWANG - Sari, Diana Ikmah; Isyanto, Puji; Lukita, Carolyn (Jurnal Riset Akuntansi Politala, 2024)
Green accounting plays a role in company decision-making when identifying and managing the industry's impact on the environment. The research aims to provide a complete picture of the phenomenon of accounting students' literacy levels, to find out the factors that influence accounting students' literacy levels, and to reveal the level of concept implementation. green accounting, and see the impact on the quality of accounting student graduates. This research applies a approach phenomenological. The primary data source is the result of interviews with informants. Data analysis technique using source triangulation. Data analysis tools from FGD activities and deep interviews. The research results concluded that accounting students' literacy regarding the qualitative characteristics of information is quite high, principles of green accounting are still low, and report components of green accounting and the importance of green accounting are still very low. This is due to a lack of student interest, some classes have not provided complete material, and there is still a lack of student research on the theme of green accounting. The results of literacy have a significant positive impact on the quality of accounting student graduates. This research implies that the Accounting Study Program is carrying out curriculum evolution to improve it. Inclusive interpretation is very important for higher education including lecturer literacy, while this research only focuses on student literacy.